Uptake of Pb(II) ion From Aqueous Solution Using Silk Cotton Hull Carbon: An Agricultural Waste Biomass - R. Shanmugavalli; P. S. Syed Shabudeen; R. Venckatesh; K. Kadirvelu; S. Madhavakrishnan; S. Pattabhi (E-Journal of Chemistry)
Activated carbon prepared from silk cotton hull (SCH) was used for the adsorptive removal of Pb(II) ion from aqueous solution. The raw material used for the preparation of activated carbon is the waste of agricultural product; the production of this carbon is expected to be economically feasible. Parameters such as agitation time, metal ion concentration, adsorbent dose, pH and Particle size were studied. Adsorption equilibrium was reached within 80 min for 10, 20, 30 and 40mg/l of Pb(II) ion with 50mg of carbon per mL of solution. Adsorption parameters were determined using both Langmuir and Freundlich isotherm models. The adsorption efficiency reached 100% for 20, 30 and 40mg/l of Pb(II) ion with 120, 140 and 150mg of carbon. Pb(II) ion removal increased as the pH increased from 2 to 5 and remains constant up to pH 10. Desorption studies were also carried out with dilute hydrochloric acid to know the mechanism of adsorption. Quantitative desorption of Pb(II) ion from carbon indicates that adsorption of metal ion is by ion-exchange. Efficiency of the adsorption of SCH was also studied with Pb containing industrial wastewater by varying pH and carbon concentration.